Das Vermengen der Rohstoffe zur Pigmentenherstellung in einem Mischer mit Stochastischer Behälterbewegung - Kuchler, Milan; Kaspar, Tomáš (Univerzita Pardubice, 1999)
The paper deals with effects of time ans intensity of mixing in preparation of threecomponent pigment mixtures. The experiments were carried out in a mixer with stochastic movement of vessel and evaluated by indirect colourimetric method. Economic aspects of the process were investigated too. The results obtained enable finding the optimum combination of time and intensity of mixing for preparation of mixtures of required degree of blending. From economic point of view, the highest-intensity mixing process proved to be the best with the "dyna-Mischer" apparatus.
Keywords: míchání; pigmenty; tříkomponentové směsi; ekonomické aspekty